Pengaruh Keberadaan Warung Internet di Lingkungan SMA Negeri 1 Tanah Abang Kabupaten Penukal Abab Lematang Ilir (PALI) - Basorudin; Antoni Pribadi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Development of Education Quality Improvement by Implementing Internet Cafes in Rural Areas makes it easier for local residents, including students at SMA Negeri 1 Tanah Abang, Penukal Abab Lematang Ilir (PALI) to communicate and find information. This internet cafe or internet cafe is accompanied by an internet network so that users can access websites, blogs, micro blogging sites, e-mail, Yahoo Messenger, Gtalk, Zoom and so on. The development of this internet cafe uses data collection methods by taking data from high school students Negeri 1 Tanah Abang, Penukal Abab Lematang Ilir (PALI) Regency, totaling 60 people. This research itself uses quantitative methods. The purpose of this research is to determine the quality of student learning in the presence of an internet cafe. Based on a questionnaire that was distributed to 60 students, the existence of an internet cafe and the impact of the internet cafe on SMA Negeri 1 Tanah Abang, Penukal Abab Lematang Ilir (PALI) was highly appreciated by most students who thought that the existence of an internet cafe had a good effect on their learning activities. In addition to studying, they can also relieve fatigue from studying all day with entertainment in the internet cafe.